Religiusitas dan Psychological Well‐Being Pada Korban Gempa - Sukma Adi Galuh Amawidyati; Muhana Sofiati Utami (Jurnal Psikologi, 2007)
The purpose of this study is to examine the correlation between religiousity and psychological well‐being on earthquake survivor at Yogyakarta. Several studies show that religiousity give some benefits to reach well‐being. Both of variables are measured by Psychological Well‐Being Scale and Religiousity Scale. The result shows there is positive correlation between religiousity and psychological well‐being(r=0, 505; p